Gender differentials in cricket farming and its impact on household food security levels in East Africa. - Nancy Ndung'u; Hezron Isaboke; Wilckyster Nyarindo; Mark Otieno; Mathew Gicheha; John Kinyuru (PLoS ONE)
Crickets, as one of the edible insects, represent a promising alternative for enhancing food security through direct human consumption or as livestock feed. This study investigated the impact of cricket farming on household food security in Kenya and Uganda, focusing on a sample of 187 cricket farmers and 457 non-farmers. Utilizing the Food Insecurity Experience Scale and the Food Consumption Score, the research assesses dimensions of food access, stability, utilization, and availability. An endogenous switching regression model was employed to analyze the influence of gender of cricket farming decision-makers and participation in cricket farming on food security outcomes. For male decision-makers, key determinants for adoption included awareness, the availability of processing technology, ready markets, and perceived risks. Female decision-makers were more significantly influenced by awareness, training opportunities, perceived benefits, and social norms. Female decision-makers who engaged in cricket farming (Y1 = 1.756) exhibited a higher levels of household food security compared to non-adopters (Y0 = 1.567), yielding a significant positive treatment effect (ATT = 0.188). In contrast, male adopters experienced a slight decrease in food security, reflecting a negative effect (ATT = -0.516). This study highlights the importance of gender differences in food security outcomes and informs policy initiatives aimed at promoting sustainable food security through cricket farming. Targeted training is recommended to enhance female farmers' skills and improve productivity as a proxy for food security. Interventions should promote group association and establish aggregation centers at the policy level to enhance access to resources and market linkages for male farmers.